INOVASI PEMBELAJARAN AKIDAH AKHLAK MENGGUNAKAN METODE ROLE PLAY DALAM MENINGKATKAN PRESTASI BELAJAR SISWA - Ansori, Ansori (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2018)
The use of various methods will greatly help students in achieving learning goals. As role play method is one way mastery of learning materials through the development of imagination and appreciation of students on learning materials. Data collection techniques in this study are observation, interviews, and documentation. To analyze the data in this research using data analysis technique of Miles and Huberman model that is data reduction (Data Reduction), data presentation (Data Display) and conclusion (Conclution Drawing / verification) The findings in this research is innovation of role play method can change paradigm to the new paradigm so that the role of the teacher is more as a facilitator, counselor, consultant, and comrade study Flexible schedule, open as needed Learning directed by students themselves Problem-based, project, real world, real action, and reflection Design and investigation. Computers as tools, and dynamic media presentations.